Analisis prinsip-prinsip fiqih serta relevansinya dalam menyelesaikan persoalan ekonomi modern sebagai landasan pensyariatan hukum islam - Taruna, Virgin Early Hera (Maliki Interdisciplinary Journal, 2025)
Fiqh principles are legal guidelines derived from the Qur’an, Hadith, and the istinbat methods of scholars, which include the values of honesty, justice, transparency, benefit, and the prohibition of harming others. These principles are an important basis for assessing and directing economic activities to comply with sharia provisions. In its relevance to the modern economic context, marked by the emergence of digital transactions, fintech, and various new financial instruments, fiqh plays a role as a framework for assessing the legality, ethics, and security of transactions. This literature review aims to analyze the principles of fiqh and their relevance in providing solutions to modern economic issues as the basis for Islamic law. The results of this study show that fiqh has the flexibility to be applied to current economic developments, providing fair and welfare-oriented solutions, and serving as a strong basis for formulating Islamic economic law that is responsive to technological and social changes. This study uses literature data that can be used to answer problems. The analysis method used is qualitative, namely through a descriptive approach with data collection techniques from various sources of previous books and journals.